"Ich habe den Herrn gesehen" (Joh 20,18): ein geschlechtsspezifisches Apostolatskriterium? - Taschl-Erber, Andrea (Protokolle zur Bibel, 2005)
According to John 20:18 Mary Magdalene is the first who is commissioned by Jesus to proclaim the Easter kerygma. Her testimony ἑώρακα τὸν κύριον (cf. John 20:25; 1Cor 9:1) represents an early church formula for resurrection witnesses which constitutes a special authority, similarly to the passive formulation ὤφθη with the dative (cf. Luke 24:34; 1Cor 15:5-8). When Paul in 1Cor 9:1 legitimates his own apostolic authority with the same wording, the so established apostolic status applies to Mary Magdalene too. Therefore, according to the Pauline criteria she even can be called the first apostle. This contrasts with the Lucan concept of apostleship where she is excluded from apostolicity just because of her gender. But as the Lucan definition fundamentally influenced the later view, female apostles got out of sight in history.